Chinese medicine, Qijudihuang pill, mediates cholesterol metabolism and regulates gut microbiota in high-fat diet-fed mice, implications for age-related macular degeneration - Cao, Yanqun; Ibrahim, Khalid S.; Li, Xing; Wong, Aileen; Wu, Yi; Yu, Xu-Dong; Zhou, Xinzhi; Tan, Zhoujin; He, Zhiming; Craft, John A.; Shu, Xinhua (Frontiers in Immunology, 2023)
Background Traditional Chinese Medicines have been used for thousands of years but without any sound empirical basis. One such preparation is the Qijudihuang pill (QP), a mixture of eight herbs, that has been used in China for the treatment of various conditions including age-related macular degeneration (AMD), the most common cause of blindness in the aged population. In order to explain the mechanism behind the effect of QP, we used an AMD model of high-fat diet (HFD) fed mice to investigate cholesterol homeostasis, oxidative stress, inflammation and gut microbiota. Methods Mice were randomly divided into three groups, one group was fed with control diet (CD), the other two groups were fed with high-fat-diet (HFD). One HFD group was treated with QP, both CD and the other HFD groups were treated with vehicles. Tissue samples were collected after the treatment. Cholesterol levels in retina, retinal pigment epithelium (RPE), liver and serum were determined using a commercial kit. The expression of enzymes involved in cholesterol metabolism, inflammation and oxidative stress was measured with qRT-PCR. Gut microbiota was analyzed using 16S rRNA sequencing. Results In the majority of the lipid determinations, analytes were elevated by HFD but this was reversed by QP. Cholesterol metabolism including the enzymes of bile acid (BA) formation was suppressed by HFD but again this was reversed by QP. BAs play a major role in signaling between host and microbiome and this is disrupted by HFD resulting in major changes in the composition of colonic bacterial communities. Associated with these changes are predictions of the metabolic pathway complexity and abundance of individual pathways. These concerned substrate breakdowns, energy production and the biosynthesis of pro-inflammatory factors but were changed back to control characteristics by QP. Conclusion We propose that the ability of QP to reverse these HFD-induced effects is related to mechanisms acting to lower cholesterol level, oxidative stress and inflammation, and to modulate gut microbiota.